THE CHEMICAL COMPOSITION OF STENOTAENIA MACROCARPA ESSENTIAL OIL AND BIOACTIVITY - Baser, K. H. C.; Kiyan, T.; Demirci, B.; Demirci, F.; Duman, H. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The genus Stenotaenia of Apiaceae is represented by only one species, namely Stenotaenia macrocarpa Freyn & Sint ex. Freyn in Turkey. The subject plant material was collected from Central Anatolia: Konya – Hadim. The essential oil of the crushed seeds of S. macrocarpa were initially obtained by hydrodistillation, which was further analyzed by both GC-FID and GC-MS systems. More than hundred constituents were identified where the main constituents were revealed as octyl acetate (32.6%), octanal (16.7%), and octanol (4.3%), to the best of our knowledge for the first time. Furthermore, the essential oil was screened for its antimicrobial activity and radical scavenging activity by TLC bioautographic techniques against Escherichia coli, Bacillus cereus, Staphylococcus aureus, Candida albicans and the DPPH radical, respectively. As a result of the bioactivity screens the oil showed microbial inhibitory and radical scavenging activities at high concentrations (>100 mg/ml).